(untitled) (BIMRAD Journal, 2025)
Bangladesh has enormous stake in the Indian Ocean Region, which goes further beyond the Bay of Bengal, consisting of ever-increasing trends in global maritime trade. Thus, the maritime frontier of Bangladesh has flourished significantly keeping up with the increasing maritime trades. The safekeeping of our maritime frontier is solidifying through the development of Bangladesh Navy. This journal topic offers a comprehensive examination of the Republic of China’s Ocean Soft Power Strategy via Ocean Consciousness Propaganda to People’s Liberation Army Navy’s (PLA Navy) recent naval development, focusing on an in-depth analysis of the country’s Ocean Literacy Policy and their potential implications for Bangladesh and Bangladesh Navy. Over an assessment of the PLA Navy’s evolving capabilities and maritime ambitions through ocean literacy, this article explores potential maritime development of Bangladesh. Moreover, this article delves deeper into the dilemma -while there are prevailing government funded oceanographic research and development institutes; they are only at surface level. It would require major overhauling of different governmental policies & strategies towards building significant structures for ensuring ocean literacy over the years to come. Finally, the article covers the possible implications to begin a literacy revolution over the maritime frontier to increase ground level knowledge vis-à-vis increase naval development for Bangladesh Navy. BIMRAD Journal VOLUME 5, ISSUE 1, DEC 2024; PP-163-177